Preparation method of polylactic acid fiber for medical and health materials

By introducing nanocellulose and nanographite particles into polylactic fibers, a three-dimensional rigid network structure is formed, and supercritical carbon dioxide foaming and nanosilver loading is carried out, the problem of poor mechanical properties of polylactic fibers is solved, and medical and health materials with high mechanical properties and antibacterial properties are achieved.

CN119640429APending Publication Date: 2025-03-18MINRUI IND HOLDINGS (JIANGSU) CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411622064.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Polylactic fibers are brittle and hard at room temperature, making it difficult to meet the mechanical properties requirements of medical and health materials.

Method used

By blending nanocellulose, nanographite particles with polylactic acid and ultrasonic assisted melt spinning, a three-dimensional rigid network structure is formed. Then supercritical carbon dioxide foaming treatment and nanosilver loading were carried out, and finally impregnated and dried in the silicate solution to form polylactic fibers for medical and health materials with high mechanical properties and antibacterial properties.

Benefits of technology

It realizes the high mechanical properties and antibacterial properties of polylactic fibers, can meet the mechanical properties requirements of medical and health materials, and achieves long-term antibacterial by controlling the release rate of silver ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of polylactic acid fibers for medical and sanitary materials, and relates to the technical field of polylactic acid fibers. Nano-crystalline cellulose, nano-graphite particles and polylactic acid are blended and crosslinked, the mechanical property of a matrix is enhanced, the antibacterial property is achieved, fibers are prepared through spinning, supercritical carbon dioxide treatment is conducted for the first time, the nano-graphite particles can play a role of a nucleating agent, polylactic acid is promoted to form fine and uniform crystals, and the mechanical property of the matrix is improved. Carbon dioxide is effectively wrapped in the foaming process, a micropore structure is formed in the fiber, the mechanical property of a matrix is enhanced, then secondary supercritical carbon dioxide treatment is conducted, the nano-silver is loaded into the matrix through supercritical fluid, the antibacterial property and the mechanical property are further improved, then the nano-silver is soaked in a silicate solution, dehydration is conducted, and the nano-silver fiber is obtained. A silica gel layer is formed on the surface of the fiber, so that the mechanical property and the antibacterial property of a matrix are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polylactic acid fibers, in particular to a method for preparing polylactic acid fibers for medical and sanitary materials. Background Art

[0002] Biodegradable materials refer to polymer materials that can be eventually degraded into small molecules or water and carbon dioxide by microorganisms. Polylactic acid is a biodegradable material, commonly known as "corn fiber". It is made from crops or straws. Lactic acid is produced by biological fermentation technology and then polymerized to obtain the polymer material polylactic acid. Finally, it is made into polyester polymers by solution spinning or melt spinning. Its products can be biodegraded into carbon dioxide and water, and will not emit toxic gases after combustion. Polylactic acid is the earliest and most widely used biodegradable medical polymer material. It can participate in human metabolic reactions and eventually degrade into carbon dioxide and water. It has good biocompatibility and blood compatibility, so it has received great attention in the fields of medical care, pharmaceuticals and food packaging. However, the polylactic acid molecular chain segment is relatively rigid and has poor flexibility. It is a brittle and hard material at room temperature, which is difficult to meet the mechanical property requirements of medical and health materials. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing polylactic acid fibers for medical and sanitary materials to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing polylactic acid fibers for medical and health materials, comprising the following preparation steps:

[0005] (1) dissolving nanocellulose in deionized water, ultrasonicating at 10-18° C. for 1-3 h, adding nanographite powder, polylactic acid, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, heating to 160-200° C., and continuing ultrasonicating for 30-70 min to perform melt spinning to obtain polylactic acid fibers;

[0006] (2) subjecting the polylactic acid fiber to a supercritical carbon dioxide foaming treatment to obtain foamed polylactic acid fiber;

[0007] (3) The foamed polylactic acid fiber is immersed in a 1.5 wt% silver nitrate-ethanol solution, reacted in a supercritical carbon dioxide fluid medium, washed with deionized water for 5 to 8 times, dried at 60 to 80° C. for 6 to 10 hours, then immersed in a silicate solution, removed, and dried at 60 to 90° C. for 4 to 6 hours to obtain polylactic acid fiber for medical and health materials.

[0008] Furthermore, the frequency of the ultrasound in step (1) is 22 kHz and the power is 300-600 W.

[0009] Furthermore, the molecular weight of the polylactic acid in step (1) is 9×10 4 .

[0010] Furthermore, the process parameters of the melt spinning in step (1) are: temperature 235° C., speed 1550 m / min, and 3.2 times heat stretching in an oil bath at 66° C.

[0011] Furthermore, in step (1), the mass ratio of the nanocellulose, deionized water, nanographite powder, polylactic acid, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 0.2-1:50:0.5-1:50-100:0.1.

[0012] Furthermore, the process steps of the supercritical carbon dioxide foaming treatment in step (2) are as follows: at 50° C., carbon dioxide is introduced to adjust the gas pressure to 10-20 MPa, the pressure is maintained for 80-180 minutes, and then foaming is performed at 130° C. for 30-70 seconds.

[0013] Furthermore, the reaction conditions in step (3) are as follows: temperature of 50-90° C., pressure of 20 MPa, and time of 80-200 min.

[0014] Furthermore, the preparation method of the silicate solution in step (3) is as follows: ethyl orthosilicate, sodium acetate, ethanol and deionized water are mixed in a mass ratio of 10:1-4:15-20:6-10, and the pH value of the solution is adjusted to 3-4 with hydrochloric acid solution.

[0015] Furthermore, in step (3), the foamed polylactic acid fiber is immersed in a 1.5wt% silver nitrate-ethanol solution and a silicate solution in a bath ratio of 1:20 to 50.

[0016] Furthermore, in step (3), the fiber is immersed in the silicate solution for 30 to 60 minutes.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] The polylactic acid fiber of the invention is prepared by mixed spinning of nano cellulose, nano graphite particles and polylactic acid, and is treated with supercritical carbon dioxide twice to achieve the effects of antibacterial and high mechanical properties.

[0019] Firstly, nanocellulose, nanographite particles and polylactic acid are blended, and the nanocellulose molecules are gelled under the assistance of ultrasound, so that the hydroxyl groups on the nanocellulose form hydrogen bonds with the carbonyl groups of the polylactic acid, thereby cross-linking the two and forming a three-dimensional rigid network structure through hydrogen bonding, thereby enhancing the mechanical properties of the matrix, and the graphite is evenly dispersed by ultrasound, and then fixed in the matrix by the network structure, thereby achieving antibacterial properties, and then spinning to obtain fibers, and performing the first supercritical carbon dioxide treatment, in which the nanographite particles can act as nucleating agents, initiating heterogeneous nucleation in the foaming process, and providing a large number of activated nuclei for the crystallization of polylactic acid, and the rigid network structure and nanoparticles have a great influence on the mechanical properties of the matrix. The hindering effect on the movement of polylactic acid chain segments promotes the formation of fine and uniform crystals of polylactic acid and their uniform distribution in the matrix, reduces the phenomenon of particle agglomeration, and enhances the mechanical properties of the fiber. The permeability of carbon dioxide in nanoparticles is poor, so it can hinder the diffusion and escape of carbon dioxide to a certain extent. At the same time, graphite particles can improve the melt strength of polylactic acid, effectively wrap carbon dioxide during the foaming process, reduce the merging and collapse of pores, thereby increasing the pore density and reducing the pore diameter. This microporous structure can passivate defects in the polymer, reduce internal stress concentration, and increase the specific surface area of ​​the fiber, which is beneficial to the release of antibacterial particles, thereby enhancing the mechanical properties and antibacterial properties of the matrix.

[0020] Secondly, a second supercritical carbon dioxide treatment is carried out, and the nanosilver is loaded into the matrix using a supercritical fluid. As the temperature rises, the activity of the polymer molecular segments is enhanced, which prompts the carbon dioxide molecules to penetrate into the high-molecular polymer and swell it, expanding its molecular gap, making it easy for the nanosilver to enter the molecular gap of the matrix. Due to the interaction, it is adsorbed on the surface of the polymer molecules. After the pressure is released, the carbon dioxide vaporizes and evaporates, while the silver particles are retained, further improving the antibacterial properties of the matrix. At the same time, the second supercritical carbon dioxide treatment has a strong plasticizing effect on the high-molecular polymer, which can significantly reduce the glass transition temperature of the polymer, thereby improving the mechanical properties of the matrix. Then, it is immersed in a silicate solution, dehydrated and dried, and a silicone gel layer is formed on the fiber surface, thereby enhancing the mechanical properties and antibacterial properties of the matrix, and can control the release rate of silver ions, thereby achieving long-term antibacterial. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the polylactic acid fibers for medical and sanitary materials prepared in the following examples are as follows:

[0023] Mechanical properties: Take the same size of the embodiment and the comparative example with reference to GB / T24218.3, and use FAVIMAT-BOBOT2 fully automatic single fiber universal tester to measure the breaking strength and breaking elongation.

[0024] Antibacterial: The same size of the embodiment and the comparative example were taken to detect the antibacterial rate against Staphylococcus aureus and Escherichia coli according to the oscillation method of GB / T20944, and then left to stand for 60 days, and the antibacterial rate was detected again.

[0025] Example 1: (1) Dissolve nanocellulose in deionized water, ultrasonicate for 1 h at 10 ° C, frequency of 22 kHz, power of 300 W, add nanographite powder with a molecular weight of 9 × 10 4 Polylactic acid, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, heated to 160°C, continued ultrasonication for 30 minutes, melt-spinned at 235°C and a speed of 1550m / min, and heat-stretched 3.2 times in an oil bath at 66°C to obtain polylactic acid fibers; the nanocellulose, deionized water, nanographite powder, molecular weight 9×10 4 The mass ratio of polylactic acid and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 0.2:50:0.5:50:0.1;

[0026] (2) placing the polylactic acid fiber at 50° C., introducing carbon dioxide to adjust the gas pressure to 10 MPa, performing a supercritical carbon dioxide process, maintaining the pressure for 80 minutes, and then foaming at 130° C. for 30 seconds to obtain foamed polylactic acid fiber;

[0027] (3) TEOS, sodium acetate, ethanol, and deionized water are mixed in a mass ratio of 10:1:15:6, and the pH value of the solution is adjusted to 3 with a hydrochloric acid solution to obtain a silicate solution; the foamed polylactic acid fiber is immersed in a 1.5wt% silver nitrate-ethanol solution in a bath ratio of 1:20, and reacted in a supercritical carbon dioxide fluid medium under the following conditions: temperature of 50°C, air pressure of 20MPa, and reaction time of 80min; the fiber is washed with deionized water for 5 times, dried at 60°C for 6h, and then immersed in a silicate solution in a bath ratio of 1:20, allowed to stand for 30min, removed, and dried at 60°C for 4h to obtain polylactic acid fiber for medical and health materials.

[0028] Example 2; (1) Dissolve nanocellulose in deionized water, ultrasonicate for 2 h at 14 ° C, frequency of 22 kHz, power of 500 W, add nanographite powder with a molecular weight of 9 × 10 4 Polylactic acid, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, heated to 180°C, continued ultrasonication for 50 minutes, melt-spun at 235°C and a speed of 1550m / min, and heat-stretched 3.2 times in an oil bath at 66°C to obtain polylactic acid fibers; the nanocellulose, deionized water, nanographite powder, molecular weight 9×10 4 The mass ratio of polylactic acid and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 0.6:50:0.75:80:0.1;

[0029] (2) placing the polylactic acid fiber at 50° C., introducing carbon dioxide to adjust the gas pressure to 15 MPa, performing a supercritical carbon dioxide process, maintaining the pressure for 130 minutes, and then foaming at 130° C. for 50 seconds to obtain foamed polylactic acid fiber;

[0030] (3) TEOS, sodium acetate, ethanol, and deionized water are mixed in a mass ratio of 10:2.5:17:8, and the pH value of the solution is adjusted to 3.5 with a hydrochloric acid solution to obtain a silicate solution; the foamed polylactic acid fiber is immersed in a 1.5wt% silver nitrate-ethanol solution in a bath ratio of 1:35, and reacted in a supercritical carbon dioxide fluid medium under the following conditions: temperature of 70°C, air pressure of 20 MPa, and reaction time of 140 min; the fiber is washed with deionized water for 7 times, dried at 70°C for 8 h, and then immersed in a silicate solution in a bath ratio of 1:35, allowed to stand for 45 min, removed, and dried at 80°C for 5 h to obtain polylactic acid fiber for medical and health materials.

[0031] Example 3; (1) Dissolve nanocellulose in deionized water, ultrasonicate for 3 h at 18 ° C, frequency of 22 kHz, power of 600 W, add nanographite powder with a molecular weight of 9 × 10 4 Polylactic acid, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, heated to 200°C, continued ultrasonication for 70 minutes, melt-spun at 235°C and a speed of 1550m / min, and heat-stretched 3.2 times in an oil bath at 66°C to obtain polylactic acid fibers; the nanocellulose, deionized water, nanographite powder, molecular weight 9×10 4 The mass ratio of polylactic acid and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1:50:1:100:0.1;

[0032] (2) placing the polylactic acid fiber at 50° C., introducing carbon dioxide to adjust the gas pressure to 20 MPa, performing a supercritical carbon dioxide process, maintaining the pressure for 180 min, and then foaming at 130° C. for 70 s to obtain foamed polylactic acid fiber;

[0033] (3) TEOS, sodium acetate, ethanol, and deionized water are mixed in a mass ratio of 10:4:20:10, and the pH value of the solution is adjusted to 4 with a hydrochloric acid solution to obtain a silicate solution; the foamed polylactic acid fiber is immersed in a 1.5wt% silver nitrate-ethanol solution in a bath ratio of 1:50, and reacted in a supercritical carbon dioxide fluid medium under the following conditions: temperature of 90°C, air pressure of 20MPa, and reaction time of 200min; the fiber is washed with deionized water, dried at 80°C for 10h, and then immersed in a silicate solution in a bath ratio of 1:50, allowed to stand for 60min, removed, and dried at 90°C for 6h to obtain polylactic acid fiber for medical and health materials.

[0034] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different, and step (1) is changed to: nano graphite powder with a molecular weight of 9×10 4 The polylactic acid and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are mixed, heated to 180°C, ultrasonicated for 50 min at a frequency of 22 kHz and a power of 500 W, melt-spun at 235°C and a speed of 1550 m / min, and heat-stretched 3.2 times in an oil bath at 66°C to obtain polylactic acid fibers; the deionized water, nano-graphite powder, and a molecular weight of 9×10 4 The mass ratio of polylactic acid and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 50:0.75:80:0.1; the remaining steps are the same as those in Example 2.

[0035] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different, and step (1) is changed to: dissolving nanocellulose in deionized water, ultrasonically treating for 2 h at 14 ° C, a frequency of 22 kHz, and a power of 500 W, adding a molecular weight of 9×10 4 Polylactic acid, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, heated to 180°C, continued ultrasonication for 50 minutes, melt-spun at 235°C and a speed of 1550m / min, and heat-stretched 3.2 times in an oil bath at 66°C to obtain polylactic acid fibers; the nanocellulose, deionized water, and a molecular weight of 9×10 4 The mass ratio of polylactic acid and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 0.6:50:80:0.1; the remaining steps are the same as those in Example 2.

[0036] Comparative Example 3; The difference between Comparative Example 3 and Example 2 is that there is no step (2); the remaining steps are the same as Example 2.

[0037] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: tetraethyl orthosilicate, sodium acetate, ethanol and deionized water are mixed in a mass ratio of 10:2.5:17:8, and the pH value of the solution is adjusted to 3.5 with hydrochloric acid solution to obtain a silicate solution; the foamed polylactic acid fiber is immersed in a 1.5wt% silver nitrate-ethanol solution at a bath ratio of 1:35, allowed to stand for 140 minutes, washed with deionized water 7 times, dried at 70°C for 8 hours, and then immersed in a silicate solution at a bath ratio of 1:35, allowed to stand for 45 minutes, removed, and dried at 80°C for 5 hours to obtain polylactic acid fiber for medical and health materials; the remaining steps are the same as those in Example 2.

[0038] Comparative Example 5; The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: mix tetraethyl orthosilicate, sodium acetate, ethanol, and deionized water in a mass ratio of 10:2.5:17:8, and adjust the solution pH to 3.5 with hydrochloric acid solution to obtain a silicate solution; immerse the foamed polylactic acid fiber in the silicate solution at a bath ratio of 1:35, let it stand for 45 minutes, remove it, and dry it at 80°C for 5 hours to obtain polylactic acid fiber for medical and health materials; the remaining steps are the same as Example 2.

[0039] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that step (3) is different. Step (3) is changed to: the foamed polylactic acid fiber is immersed in a 1.5wt% silver nitrate-ethanol solution at a bath ratio of 1:35, and reacted in a supercritical carbon dioxide fluid medium. The conditions are as follows: temperature is 70°C, air pressure is 20MPa, time is 140min, washed with deionized water 7 times, and dried at 70°C for 8h to obtain polylactic acid fiber for medical and health materials; the remaining steps are the same as Example 2.

[0040] Effect example

[0041] Table 1 below shows the performance analysis results of the polylactic acid fibers for medical and sanitary materials using Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0042] Table 1

[0043]

[0044] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention utilizes nanocellulose, nanographite particles and polylactic acid for blending, and under the assistance of ultrasound, the nanocellulose and polylactic acid are cross-linked to form a three-dimensional rigid network structure through hydrogen bonding, thereby enhancing the mechanical properties of the matrix, and the graphite is evenly dispersed by ultrasound, and then fixed in the matrix by the network structure, thereby achieving antibacterial properties, and then spinning to obtain fibers, and performing the first supercritical carbon dioxide treatment, wherein the nanographite particles can act as a nucleating agent, and in the foaming process, heterogeneous nucleation is induced to provide a large number of activated nuclei for the crystallization of polylactic acid, thereby promoting the formation of fine and uniform crystals of polylactic acid, and uniformly distributed in the matrix, thereby enhancing the mechanical properties of the fiber, and carbon dioxide can hinder the diffusion and escape of carbon dioxide to a certain extent, and at the same time, the graphite particles can improve the melt strength of polylactic acid, effectively wrap carbon dioxide during the foaming process, reduce the merging and collapse of bubbles, thereby By increasing the pore density and reducing the pore diameter, this microporous structure can passivate the defects in the polymer and increase the specific surface area of ​​the fiber, which is beneficial to the release of antibacterial particles, thereby enhancing the mechanical properties and antibacterial properties of the matrix. Then, a second supercritical carbon dioxide treatment is carried out, and the nanosilver is loaded into the matrix using a supercritical fluid. As the temperature rises, the activity of the polymer molecular segments is enhanced, which promotes the carbon dioxide molecules to penetrate into the high molecular polymer and swell it, making it easy for the nanosilver to enter the molecular gaps of the matrix. Due to the interaction, it is adsorbed on the surface of the polymer molecules, further improving the antibacterial properties of the matrix. At the same time, the second supercritical carbon dioxide treatment has a strong plasticizing effect on the high molecular polymer, thereby improving the mechanical properties of the matrix. Then, it is immersed in a silicate solution, dehydrated and dried, and a silicone gel layer is formed on the fiber surface, thereby enhancing the mechanical properties and antibacterial properties of the matrix, and can control the release rate of silver ions, thereby achieving long-term antibacterial.

[0045] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing polylactic acid fiber for medical and health materials, characterized in that: The method comprises the following preparation steps: (1) dissolving nanocellulose in deionized water, ultrasonicating at 10-18° C. for 1-3 h, adding nanographite powder, polylactic acid, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, heating to 160-200° C., and continuing ultrasonicating for 30-70 min to perform melt spinning to obtain polylactic acid fibers; (2) subjecting the polylactic acid fiber to a supercritical carbon dioxide foaming treatment to obtain foamed polylactic acid fiber; (3) The foamed polylactic acid fiber is immersed in a 1.5 wt% silver nitrate-ethanol solution, reacted in a supercritical carbon dioxide fluid medium, washed with deionized water for 5 to 8 times, dried at 60 to 80° C. for 6 to 10 hours, then immersed in a silicate solution, removed, and dried at 60 to 90° C. for 4 to 6 hours to obtain polylactic acid fiber for medical and health materials.

2. The method for preparing polylactic acid fiber for medical and health materials according to claim 1, characterized in that: The frequency of the ultrasound in step (1) is 22kHz and the power is 300-600W.

3. The method for preparing polylactic acid fiber for medical and health materials according to claim 1, characterized in that: The molecular weight of the polylactic acid in step (1) is 9×10 4 .

4. The method for preparing polylactic acid fiber for medical and health materials according to claim 1, characterized in that: The process parameters of the melt spinning in step (1) are: temperature 235° C., speed 1550 m / min, and 3.2 times hot stretching in an oil bath at 66° C.

5. The method for preparing polylactic acid fiber for medical and health materials according to claim 1, characterized in that: The mass ratio of the nanocellulose, deionized water, nanographite powder, polylactic acid and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate in step (1) is 0.2-1:50:0.5-1:50-100:0.

1.

6. The method for preparing polylactic acid fiber for medical and sanitary materials according to claim 1, characterized in that: The process steps of the supercritical carbon dioxide foaming treatment in step (2) are as follows: at 50° C., carbon dioxide is introduced to adjust the gas pressure to 10-20 MPa, the pressure is maintained for 80-180 minutes, and then foaming is performed at 130° C. for 30-70 seconds.

7. The method for preparing polylactic acid fiber for medical and sanitary materials according to claim 1, characterized in that: The reaction conditions of step (3) are as follows: temperature of 50-90° C., air pressure of 20 MPa, and time of 80-200 min.

8. The method for preparing polylactic acid fiber for medical and sanitary materials according to claim 1, characterized in that: The preparation method of the silicate solution in step (3) is as follows: ethyl orthosilicate, sodium acetate, ethanol and deionized water are mixed in a mass ratio of 10:1-4:15-20:6-10, and the pH value of the solution is adjusted to 3-4 with a hydrochloric acid solution.

9. The method for preparing polylactic acid fiber for medical and sanitary materials according to claim 1, characterized in that: In step (3), the foamed polylactic acid fiber is immersed in a 1.5wt% silver nitrate-ethanol solution and a silicate solution in a bath ratio of 1:20 to 50.

10. The method for preparing polylactic acid fiber for medical and sanitary materials according to claim 1, characterized in that: In step (3), the fiber is immersed in the silicate solution for 30 to 60 minutes.

Citation Information

Cited By

  • Modified degradable fiber and preparation method thereof

    CN121023668A